2013
DOI: 10.1021/bm400291s
|View full text |Cite
|
Sign up to set email alerts
|

Laccase-Mediated Coupling of Nonpolar Chains for the Hydrophobization of Lignocellulose

Abstract: We investigate the use of laccase enzymes to couple short nonpolar chains containing aromatic groups onto flax fibers and nanofibrillated cellulose (NFC) with different lignin contents. Trametes villosa , Pycnoporus cinnabarinus , and Myceliophthora thermophila were used to facilitate surface coupling and to produce materials with different levels of hydrophobicity. Heat treatment of fiber webs after lacccase-mediated coupling markedly increased the resistance to water absorption. The highest hydrophobization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 35 publications
0
27
0
Order By: Relevance
“…However, such a functionalisation may not be adequately applied if the integrity of the cellulose polymer chain is to be preserved without a side-reaction such as intermolecular crosslinking (Garcia-Ubasart, Vidal, Torres, & Rojas, 2013). Thus, the phosphorylation of cotton (Tzanov et al, 2002) or NFC (Božič, Liu, Mathew, & Kokol, 2014) using site-specific hexokinase-mediated reactions in the presence of phosphoryl donor adenosine-5 -triphosphate was achieved with low DS of up to 0.43 at the C6 hydroxyl group of the cellulose glucopyranose ring.…”
Section: Introductionmentioning
confidence: 99%
“…However, such a functionalisation may not be adequately applied if the integrity of the cellulose polymer chain is to be preserved without a side-reaction such as intermolecular crosslinking (Garcia-Ubasart, Vidal, Torres, & Rojas, 2013). Thus, the phosphorylation of cotton (Tzanov et al, 2002) or NFC (Božič, Liu, Mathew, & Kokol, 2014) using site-specific hexokinase-mediated reactions in the presence of phosphoryl donor adenosine-5 -triphosphate was achieved with low DS of up to 0.43 at the C6 hydroxyl group of the cellulose glucopyranose ring.…”
Section: Introductionmentioning
confidence: 99%
“…The monomers of the laccase-mediated grafting can be divided into two categories, phenolic compounds and amine compounds. It is generally reported that the laccase-mediated grafting of phenolic monomers onto lignocellulosic materials has been successfully achieved to endow such polymers with novel functions [18][19][20][21][22][23][24][25]. However, the homopolymerization of these phenols will occur inevitably accompanied with the desired enzymatic grafting reaction.…”
Section: Estimation Of Grafting Percentage Via Elemental Analysismentioning
confidence: 99%
“…Studies show that lignin is a suitable substrate for laccase and the phenolic sites of lignin molecules can be oxidized to phenoxyl radicals by laccase [17]. With the laccasecatalyzed oxidation of lignin moieties rich on the surface, the lignocellulosic materials could be activated to create a radical-rich reactive surface to which oxidized (radical-containing) phenolic molecules of interest by laccase simultaneously can be grafted [18][19][20][21][22][23]. Natural jute fiber, a widely used lignocellulosic bioresource with lignin content of 14-20%, also has the potential to be modified by this green biotechnology for endowing it with better performance or novel functions [24,25].…”
mentioning
confidence: 99%
“…Garcia-Ubasart et al [55] showed that the hydrophobicity of nanofibrillated cellulose can be controlled through laccase-mediated coupling of different short, hydrophobic chains to its surface. The coupling reaction, catalyzed by laccase, showed that hydrophobization could be maximized by coupling dodecyl 3,4,5-trihydroxybenzoate (HB-C12) with flax fiber-based nanofibrillated cellulose [55]. The resulting water contact angles of the fiber webs were found to be 80-96 degrees, significantly greater than those of the control [55].…”
Section: Enzymatic Modification Of Cnfmentioning
confidence: 99%
“…The coupling reaction, catalyzed by laccase, showed that hydrophobization could be maximized by coupling dodecyl 3,4,5-trihydroxybenzoate (HB-C12) with flax fiber-based nanofibrillated cellulose [55]. The resulting water contact angles of the fiber webs were found to be 80-96 degrees, significantly greater than those of the control [55]. Cusola et al [56] also manipulated surface hydrophobicity through applying a novel, multicomponent colloidal system comprised of laccase, hydrophobic dodecyl 3,4,5-trihydroxybenzoate (LG), and dispersant (sulfonated lignin) to couple LG onto the surface of CNF.…”
Section: Enzymatic Modification Of Cnfmentioning
confidence: 99%